2007
DOI: 10.4012/dmj.26.361
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of Streptococcus sanguinis to Dental Implant and Restorative Materials in vitro

Abstract: Bacterial adhesion to tooth surfaces or dental materials starts immediately upon exposure to the oral environment. The aim of this study, therefore, was to compare the adhesion of Streptococcus sanguinis to saliva-coated human enamel and dental materials -during a one-hour period -using an in vitro flow chamber system which mimicked the oral cavity. After fluorescent staining, the number of adhered cells and their vitality were recorded. The dental materials used were: titanium (Rematitan M), gold (Neocast 3),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
3
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 26 publications
0
60
3
6
Order By: Relevance
“…There are at least 2 methods of inhibiting the formation of microbial plaque: the first is to inhibit the initial attachment of bacteria; the second is to inhibit the colonization of bacteria, which involves surface antimicrobial activity. Hauser-Gerspach et al reported that release of F ions from resin composites decreased bacterial adhesion 25) . In earlier studies, we demonstrated a number of mechanisms capable of inhibiting biofilm accumulation on a Ti surface: coating with alumina for inhibition of initial attachment 21) , application of F + -implantation 33) and immobilization of anti-microbial peptides 42) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are at least 2 methods of inhibiting the formation of microbial plaque: the first is to inhibit the initial attachment of bacteria; the second is to inhibit the colonization of bacteria, which involves surface antimicrobial activity. Hauser-Gerspach et al reported that release of F ions from resin composites decreased bacterial adhesion 25) . In earlier studies, we demonstrated a number of mechanisms capable of inhibiting biofilm accumulation on a Ti surface: coating with alumina for inhibition of initial attachment 21) , application of F + -implantation 33) and immobilization of anti-microbial peptides 42) .…”
Section: Discussionmentioning
confidence: 99%
“…While much information is available on bacterial adherence to enamel or Ti [22][23][24][25] , information regarding bacterial adherence to TZP is limited 26,27) . Furthermore, little is known about in vitro adherence activity of periodontopathic bacteria to TZP.…”
Section: Introductionmentioning
confidence: 99%
“…We think that the pellicle composition may vary between different restorative materials; and, consequently, different pellicle components such as B and Al would act as binding receptors for bacterial cells. Some dental restorations release metallic or fluoride ions into the environment with a possible influence on the vitality of the adherent bacteria 12) . Glass ionomer cements (GICs), which are widely used as a restorative material, contain a high percentage of F. It was reported that the population of S. mutans on the surface of GIC fillings is lower than that on composite resin fillings 18) .…”
Section: Discussionmentioning
confidence: 99%
“…The sterilized saliva was stored at 4ºC. Before use, the pH was adjusted to 7.1-7.3 with phosphate buffer (0.067 mol/L Na 2HPO4, 0.067 mol/L KH2PO4) 12) .…”
Section: Preparation Of Saliva For Coating Of Samplesmentioning
confidence: 99%
“…For this reason, these models are good tools in order to study species-specific infections or mono-infections, but not very useful to study mixed anaerobic infections such as peri-implantitis. [Maddikeri, 2008 #56] S. sanguinis Ti, Au, and ceramic and composite dental materials (Hauser-Gerspach et al, 2007) …”
Section: Surface Modifications To Prevent Bacterial Adhesion and Biofmentioning
confidence: 99%